Визначення та трасування об’єктів у відеоматеріалі - Грицаков, І. В.; Котельніков, І. В. (ХНУРЕ, 2024)
In today's world, there is a large amount of video material that needs to be analyzed and processed to obtain valuable information. One of the key stages of video processing is object tracking, which allows you to determine the position and movement of objects in a sequence of frames. Tracking is widely used in fields such as video surveillance, augmented reality, video games, video stabilization, and many others.
Keywords: трасування об’єктів у відеоматеріалі; відеоматеріал